European Agency Statistics on Inclusive Education: 2016 Dataset Cross-Country Report - European Agency For Special Needs And Inclusive Education (Zenodo, 2018)
This report presents the analysis of the 2016 dataset collected via the European Agency Statistics on Inclusive Education (EASIE) activities and uses the country data available on the EASIE Data web area. The previous report, 2014 Dataset Cross-Country Report, is also available online. This report focuses on the 2016 dataset. The data from participating countries is from the 2014/2015 school year and the dataset was processed from 2016 onwards. The report presents data relating to 17 indicators that were identified and agreed upon with the national data experts. The indicators are based on three areas of country data: Population and enrolment data taken from Table 1. Age sample data (9- and 15-year-olds) taken from Table 2. Data on pupils with an official decision of special educational needs (SEN) taken from Table 3, including identification rates and distributions of educational placements taken from Table 3, along with gender and International Standard Classification of Education (ISCED) breakdowns of this data taken from Table 4. The report is structured around these three areas, with descriptive texts and figures presenting all available country data for each indicator. The information available from the indicators provides insights into the following issues relating to inclusive education: Access to mainstream education – what proportion of pupils, including those with an official decision of SEN, go to a mainstream school? Access to inclusive education – what proportion of pupils, including those with an official decision of SEN, spend the majority of their time with their peers in mainstream classrooms? Gender issues – are there differences in the proportion of males and females with an official decision of SEN? ISCED issues – are there differences between ISCED 1 and ISCED 2 in the proportion of pupils with an official decision of SEN? The report covers data from 30 participating countries: Belgium (Flemish community), Croatia, Cyprus, Czech Republic, Denmark, Estonia, Finland, France, Germany, Hungary, Iceland, Ireland, Italy, Latvia, Lithuania, Luxembourg, Malta, Netherlands, Norway, Poland, Portugal, Slovakia, Slovenia, Spain, Sweden, Switzerland, United Kingdom (England), United Kingdom (Northern Ireland), United Kingdom (Scotland) and United Kingdom (Wales). Download the report below in English. : This publication has been funded with support from the European Commission. This publication reflects the views only of the author, and the Commission cannot be held responsible for any use which may be made of the information contained therein. : {"references": ["European Agency for Special Needs and Inclusive Education, 2018. European Agency Statistics on Inclusive Education: 2016 Dataset Cross-Country Report. (J.\u00a0Ramberg, A.\u00a0L\u00e9n\u00e1rt, and A.\u00a0Watkins, eds.). Odense, Denmark"]}